Model-based design and operation of coaxial probe-type microwave reactor toward large-scale production of nanoparticles. (31st December 2022) - Shi, Wei-Dong; Wang, Chang; Yan, Wei-Cheng
Highlights: A novel microwave reactor with coaxial probe for nanoparticle production was designed. Maxwell's wave equations were coupled with traditional reactor model. The performance of the designed reactor was evaluated. Temperature and electromagnetic field distribution followed wavy fluctuation patterns. Agitation was suggested to eliminate hot spots in a large-scale production. Abstract: In this study, a novel microwave reactor with coaxial probe embedded for nanoparticle synthesis was designed and analyzed by numerical simulation method. Numerical model considering electromagnetic wave transmission and heat transfer inside the reactor was developed by coupling Maxwell's wave equations with traditional reactor model. The model was validated by comparing simulation results with experimental data from a lab scale coaxial microwave reactor. Characteristics of microwave transmission and heat transfer were studied in terms of electromagnetic filed distribution, electromagnetic power loss and temperature distribution. The results showed that the temperature distribution displayed wavy fluctuation patterns which was consistent with the microwave distribution. The strength of both electric field and magnetic field attenuated along the radial direction. Investigations on the effects of key parameters including microwave power intensity, frequency, probe configuration and solution dielectric properties suggested that proper power with frequency of 2.45 GHz and probe with configuration of ϕ 2 * = 0.08333 may give better performance for efficient microwave heating in the present reactor. Proper dielectric constant and dielectric loss factor should be adjusted to avoid the overheating even the average temperature is fulfilled the requirement. Temperature distribution and microwave energy loss in reactors with various capacities and multi-probe array were explored to shed some lights on the scale-up of the proposed microwave reactor for mass production of nanomaterials. In addition, performance of the designed reactor was evaluated by comparing with readily available cavity-type microwave reactor, showing that better electromagnetic uniformity can be obtained by probe-type reactor.